Comparison of Bacterial Etiology with Antibiogram of Blood Stream Infection between Adult and Paediatric Group at a Tertiary Care Hospital in Bangladesh (Bangladesh Journal of Medical Science, 2023)
Background: Timely understanding of bacterial profiles and the change of antimicrobial resistance provide an important guidance for effective and optimized use of antibiotics in local healthcare systems.Objective: The purpose of this study was to compare of bacterial etiology with antibiogram of blood stream infection between adult and paediatric.Methodology: This cross-sectional study was conducted in the department of Microbiology at Monno Medical College, Manikganj, Bangladesh during the period from January 2019 to December 2019 for duration of one year. In adult and pediatric patient blood was collected according to blood collection guidelines and inoculated into BacT/ALERT FA plus and BacT/ALERT PF plus aerobic blood culture bottles respectively. After collection these bottles were immediately incubated in BacT/ALERT 3D (manufactured by bioMerieoux, France) a fully automated blood culture system. Antimicrobial susceptibility test was done for all isolated bacteria by disc diffusion method.Result: A total number of 178 patients were recruited, among them 12 (7%) yielded growth of different bacteria. The culture positive cases were found in 7 (4%) in Paediatric group and 5 (3%) in adult age group. The most predominant identified bacteria in Paediatric group was Escherichia Coli which showed highly sensitive to imipenum, amikacin, linezolid, gentamicin (n=3, 100%). In adult group the most predominant isolated bacteria was Streptococci species which showed high sensitive to imipenum, linezolid, gentamicin 4 (80%) considerable sensitive to ciprofloxacin, tetracycline, cefotaxime, cefuroxime 3(60.0%).Conclusion: In conclusion the most common bacteria isolated from blood stream infection in adult and paediatric group are Streptococci species and Escherichia Coli respectively.Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 869-875